2008
DOI: 10.1017/s0022029908003300
|View full text |Cite
|
Sign up to set email alerts
|

Production of hydrogen peroxide by a small molecular mass compound in milk from Holstein cows with high and low milk somatic cell count

Abstract: Mastitis is the most frequent and prevalent production disease in dairy herds in developed countries. Based on a milk somatic cell count (SCC) of either >300,000 or <200,000 cells/ml in this study, we defined the quarter as either inflamed or uninflamed, respectively. The electrical conductivity (EC) of milk was used as an indicator of udder epithelial cell damage. We determined the amount of H2O2 produced by utilizing a small molecular weight compound in milk, and examined the characteristics of H2O2 producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Sulfhydryl oxidases are plentiful, and some potentially have a role in innate immunity geared toward offspring protection (Isaacs et al ., 1984), but ultimately this enzyme oxidizes free sulfhydryl groups by using oxygen as an electron acceptor with hydrogen peroxide being produced as a result. Hydrogen peroxide production in milk is reduced in other periods of higher blood and milk interactivity, including mammary inflammation caused by mastitis (Sakai et al ., 2008), and hence a decrease in sulfhydryl oxidase abundance is in line with our suggestion that the blood-milk barrier may be affected by feeding GPM.…”
Section: Discussionsupporting
confidence: 91%
“…Sulfhydryl oxidases are plentiful, and some potentially have a role in innate immunity geared toward offspring protection (Isaacs et al ., 1984), but ultimately this enzyme oxidizes free sulfhydryl groups by using oxygen as an electron acceptor with hydrogen peroxide being produced as a result. Hydrogen peroxide production in milk is reduced in other periods of higher blood and milk interactivity, including mammary inflammation caused by mastitis (Sakai et al ., 2008), and hence a decrease in sulfhydryl oxidase abundance is in line with our suggestion that the blood-milk barrier may be affected by feeding GPM.…”
Section: Discussionsupporting
confidence: 91%
“…57 However, for the system to function, H 2 O 2 must be present. Sakai et al 58 recently showed that inflammation of the mammary gland caused a decrease in H 2 O 2 production in milk. Therefore, the presence of E. coli and S. aureus possibly inactivated the LPO/H 2 O 2 /thiocyanate system in infected milks and caused the down-regulation of LPO.…”
Section: Discussionmentioning
confidence: 99%